The steel kiss - Deaver, Jeffery (New York : Grand Central Publishing, 2016)
Amelia Sachs is hot on the trail of a killer, chasing him through a department store in Brooklyn when an escalator malfunctions. The stairs give way and a man is horribly mangled by the gears. Sachs is forced to let her quarry escape as she jumps in to try to help save the victim. She and famed forensic detective Lincoln Rhyme soon learn, however, that the incident may not be an accident at all, but the first in a series of intentional attacks.
Keywords: Rhyme, Lincoln (Fictitious character) -- Fiction; Police -- New York (State) -- New York -- Fiction; Forensic scientists -- Fiction; Quadriplegics -- Fiction; Serial murder investigation -- Fiction; Suspense fiction; Mystery fiction